2017
DOI: 10.1111/eva.12553
|View full text |Cite
|
Sign up to set email alerts
|

Native and invasive taxa on the Pacific coast of South America: Impacts on aquaculture, traceability and biodiversity of blue mussels (Mytilus spp.)

Abstract: Gaining new knowledge of the native distributions of species (phylogeography)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 78 publications
(154 reference statements)
2
80
1
Order By: Relevance
“…Nonetheless, we are left with the fact that in ports and in natural environments in the Bay of Brest, dock mussels have probably displaced the native lineages. Michalek, Ventura, and Sanders () report impacts of hybridisation on Mytilus aquaculture in Scotland and Larraín et al () raise concerns of economic impacts in Chile. In Scotland, a recent demographic increase in M. trossulus has produced large losses to M. edulis aquaculture due to their colonisation of culture ropes and their shell being more fragile (Beaumont, Hawkins, Doig, Davies, & Snow, ; Dias et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we are left with the fact that in ports and in natural environments in the Bay of Brest, dock mussels have probably displaced the native lineages. Michalek, Ventura, and Sanders () report impacts of hybridisation on Mytilus aquaculture in Scotland and Larraín et al () raise concerns of economic impacts in Chile. In Scotland, a recent demographic increase in M. trossulus has produced large losses to M. edulis aquaculture due to their colonisation of culture ropes and their shell being more fragile (Beaumont, Hawkins, Doig, Davies, & Snow, ; Dias et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ecological and physiological studies have suggested a sympatric distribution of M. chilensis and M. edulis platensis at the southern limit of their latitudinal range (Dellatorre, Pascual, & Barón, 2007), M. edulis alleles were absent from Isla Peel (IP, 50°50′29.83″S, 74°00′41.27″W) after PAP polymorphisms (Larraín et al, ) as well as from Punta Arenas (PUCL, 53°09′16.12″S, 70°54′59.31″W) using 49 SNPs (Larraín et al, ). Also, a recent study on mitogenomes stated that both ‘morphotypes’ are conspecific regional variants and should be taxonomically termed M. platensis (Gaitán‐Espitia, Quintero‐Galvis, Mesas, & d'Elía, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The first studies of the Chilean mussel using microsatellite markers (Ouagajjou, Presa, Astorga, & Pérez, 2011) or the Cytochrome Oxidase I gene (Seguel, 2011) showed that this species is genetically different from NH Mytilus spp., and such evolutionary novelty was further corroborated by studies on the sperm structure (Oyarzún, Toro, Garrido, Briones, & Guiñez, 2014), microsatellites (e.g. Larraín, Díaz, Lamas, Uribe, & Araneda, 2014), mitochondrial DNA (Śmietanka & Burzy nski, 2017), and single nucleotide polymorphisms (SNPs; Larraín et al, 2018;Zbawicka et al, 2018). Therefore, M. chilensis is the valid nomen for this taxon that adheres to the principle of taxonomic priority since it was first described by Hupé (1854) on specimens from Concepción (Chile).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…America (e.g. Larraín et al, 2018). Genetic investigations to date have used either insufficient loci to resolve species relationships and migration (e.g.…”
Section: Late-pleistocene Divergence Between Native and Introduced mentioning
confidence: 99%